Associations between persistent organic pollutants and type 1 diabetes in youth. (May 2022) - Bresson, Sophie E.; Isom, Scott; Jensen, Elizabeth T.; Huber, Sandra; Oulhote, Youssef; Rigdon, Joseph; Lovato, James; Liese, Angela D.; Pihoker, Catherine; Dabelea, Dana; Ehrlich, Shelley; Ruzzin, Jérôme
Highlights: The contribution of POPs to type 1 diabetes (T1D) remains poorly known. We investigated the link between POPs and T1D in youth and the effects of POPs on β-cell. p, p'-DDE, p, p'-DDT, trans -nonachlor, and PCB-153 were associated with T1D with normal insulin sensitivity. p, p'-DDE and PCB-153 cause dysfunction and destruction of β-cells in vitro. Our findings suggest that POPs may play a role in T1D. Abstract: Background: Diabetes affects millions of people worldwide with a continued increase in incidence occurring within the pediatric population. The potential contribution of persistent organic pollutants (POPs) to diabetes in youth remains poorly known, especially regarding type 1 diabetes (T1D), generally the most prevalent form of diabetes in youth. Objectives: We investigated the associations between POPs and T1D in youth and studied the impacts of POPs on pancreatic β-cell function and viability in vitro . Methods: We used data and plasma samples from the SEARCH for Diabetes in Youth Case Control Study (SEARCH-CC). Participants were categorized as Controls, T1D with normal insulin sensitivity (T1D/IS), and T1D with insulin resistance (T1D/IR). We assessed plasma concentrations of polychlorinated biphenyls (PCBs) and organochlorine pesticides and estimated the odds of T1D through multivariable logistic regression. In addition, we performed in vitro experiments with the INS-1E pancreatic β-cells. Cells were treated with PCB-153 or p, p'-DDE at environmentally relevant doses. We measured insulin production and secretion and assessed the mRNA expression of key regulators involved in insulin synthesis ( Ins1, Ins2, Pdx1, Mafa, Pcsk1/3, and Pcsk2 ), glucose sensing ( Slc2a2 and Gck ), and insulin secretion ( Abcc8, Kcnj11, Cacna1d, Cacna1b, Stx1a, Snap25, and Sytl4 ). Finally, we assessed the effects of PCB-153 and p, p'-DDE on β-cell viability. Results: Among 442 youths, 112 were controls, 182 were classified with T1D/IS and 148 with T1D/IR. The odds ratios (OR) of T1D/IS versus controls were statistically significant for p, p'-DDE (OR 2.0, 95% confidence interval (CI) 1.0, 3.8 and 2.4, 95% CI 1.2, 5.0 for 2nd and 3rd tertiles, respectively), trans -nonachlor (OR 2.5, 95% CI 1.3, 5.0 and OR 2.3, 95% CI 1.1, 5.1 for 2nd and 3rd tertiles, respectively), and PCB-153 (OR 2.3, 95% CI 1.1, 4.6 for 3rd tertile). However, these associations were not observed in participants with T1D/IR. At an experimental level, treatment with p, p'-DDE or PCB-153, at concentrations ranging from 1 × 10 -15 M to 5 × 10 -6 M, impaired the ability of pancreatic β-cells to produce and secrete insulin in response to glucose. These failures were paralleled by impaired Ins1 and Ins2 mRNA expression. In addition, among different targeted genes, PCB-153 significantly reduced Slc2a2 and Gck mRNA expression whereas p, p'-DDE mainly affected Abcc8 and Kcnj11 . While treatment with PCB-153 or p, p'-DDE for 2 days did not affect β-cell viability, longer treatment progressively killed the β-cells. Conclusion: These results support a potential role of POPs in T1D etiology and demonstrate a high sensitivity of pancreatic β-cells to POPs.